PERAN ORANG TUA DALAM MEMBANTU PENCAPAIAN PERKEMBANGAN KOGNITIF ANAK SEKOLAH DASAR DI KELURAHAN SIGUHUNG KECAMATAN LUBUK BASUNG KABUPATEN AGAM - S, Ira Maisyara.; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
The problem in this research is: the lack of attention some parents of their childrens development because busyness in the works, the researchers raised concerns about: How the role of parents in helping and achieve the cognitive development of children up in Siguhung, Lubuk Basung District, Agam. The purpose of this study describe: 1) The role of parents in helping and achieve the childrens development observations. 2) The role of parents in helping and achieve the childrens development fantasy. 3) The role of parents in helping and achieve the childrens development thinking. This research was a descriptive. The population of this research was all parents who have children up at Elementary School, amounting 43 people. Techniques that used to take the sample was purposive sampling amounting 43 people. Instrument used in this study was a questionnaire. While the percentage of data analysis techniques used. The results of this research revealed that: 1) The role of parents in helping and achieve of children development observations in good categories. 2) The role of parents in helping achieve of children development fantasy was in good category. 3) The role of parents in helping achieve of children development thinking was in good category.